Reseña de: CABALLOS, A.; MELCHOR, E. (Eds.): De Roma a las Provincias: las élites como instrumento de proyección de Roma. Juan Francisco Rodríguez Neila In Honorem. - Romero Vera, Diego (Anales de Arquelogía Cordobesa, 2019)
Reseña del libro citado